2014
DOI: 10.1016/j.ajhg.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Association of REEP2 with Membranes Leads to Hereditary Spastic Paraplegia

Abstract: Hereditary spastic paraplegias (HSPs) are clinically and genetically heterogeneous neurological conditions. Their main pathogenic mechanisms are thought to involve alterations in endomembrane trafficking, mitochondrial function, and lipid metabolism. With a combination of whole-genome mapping and exome sequencing, we identified three mutations in REEP2 in two families with HSP: a missense variant (c.107T>A [p.Val36Glu]) that segregated in the heterozygous state in a family with autosomal-dominant inheritance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 39 publications
(63 reference statements)
2
67
0
7
Order By: Relevance
“…10 Our results show that KIF1A variants must be considered in patients with HSP, regardless of the mode of inheritance. The gene REEP2 was also recently associated with both dominant and recessive HSP, 24 both inheritance types being classified under SPG72. 25 Therefore, we suggest that HSP caused by dominant KIF1A variants be classified in the same group as HSP caused by recessive KIF1A variants, that is, SPG30.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our results show that KIF1A variants must be considered in patients with HSP, regardless of the mode of inheritance. The gene REEP2 was also recently associated with both dominant and recessive HSP, 24 both inheritance types being classified under SPG72. 25 Therefore, we suggest that HSP caused by dominant KIF1A variants be classified in the same group as HSP caused by recessive KIF1A variants, that is, SPG30.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously (Esteves et al, 2014). Signals were visualized with a chemiluminescence substrate (SuperSignal West Dura), or acquired with an Odyssey ClX (Li-COR).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, 15 candidate genes for ARHSP were reported and the assigned locus for HSP increased up to SPG72 (Esteves et al, 2014;Novarino et al, 2014) (Fig. 2, Tables 1 and 2).…”
Section: Spg58-spg72mentioning
confidence: 99%
“…In affected members of a large French family with ADHSP, it has been identified a heterozygous missense mutation in the REEP2 gene (Esteves et al, 2014) (Tables 1 and 2). ARHSP Forty-eight SPG loci and 41 genes responsible for ARHSP have been identified so far. Several other ARHSP loci, namely SPG14 (Vazza et al, 2000), SPG23 (Blumen et al, 2003), SPG24 (Hodgkinson et al, 2002), SPG25 (Zortea et al, 2002), SPG27 (Meijer et al, 2004;Ribaï et al, 2006), SPG32 (Stevanin et al, 2007a), and SPG45 (Dursun et al, 2009), have been identified but pathological genes are yet unknown (Tables 1 and 2).…”
Section: Spg72mentioning
confidence: 99%